NGROWOT FASTING URGENCY IN TASAWUF PERSPECTIVE AND HEALTH SCIENCE - Zahro, Alvin Nur (http://jagadalimussirry.com/, 2020)
Abstract. Ngrowot fasting is one of the fasting traditions of Java (kejawen) which is based on the Javanese calendar, with the intention to increase metaphysical spiritual power. Perpetrators of fasting may eat as normal days, but are restricted not allowed to eat from the basic ingredients of rice, can be replaced with tubers, corn, yams. This study aims to determine the urgency of fasting ngrowot in the perspective of Sufism with the relationship in health science. The method used in this research is library research which takes data from books, journals, magazines, documents or pure library research related to the object of research. Suarni's research results, 2009 showed that corn contained food fiber, essential fatty acids, isoflavones, minerals, b-carotene, essential amino acid composition, and others. The fasting of ngrowot perspective of sufism and health science can cause the fasting person to ngrowot his soul to be calmer and more enthusiastic to carry out worship to Allah SWT.